Evaluation of nurses’ knowledge toward pain management of leukemic child under chemotherapy - ahjil, Zaid; Maala, Ekbal (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To evaluate nurses' knowledge toward pain management of leukemic child in oncology wardshow were receiving chemotherapy.Methodology: A descriptive study was conducted in two hospitals on (40) nurses, who provided care for thechildren with leukemia in oncology wards (2) hospitals (Children Welfare Teaching Hospital and Child’s CentralTeaching Hospital) in Baghdad city from October 2010 up to the 27th of October 2011 for the purpose ofevaluating their knowledge towards pain management for leukemic child. A purposive "non-probabilitysample" was selected that consisted of (40) nurse who are working in oncology wards. A questionnaire formatwas used which consist of (2) parts, the first part includes demographic information of the sample and thesecond part consists of structured Items concerning nurses' knowledge toward pain management for leukemicchild which includes (3) main sections and comprised of (89) Items. Reliability and validity of questionnaire wasestimated through a pilot study and a panel of expert. The data were analyzed by using descriptive statisticalmeasures which included frequencies, percentages, and standard deviation, as well as the use of inferentialstatistical measures which include the chi- square test.Results: The results revealed inadequate nurse's knowledge about pain management for leukemic child underchemotherapy, two third (75 %) of the sample has poor knowledge toward pharmacological and nonpharmacological pain management methods.Recommendations: Based on the results of research, the study recommends initiating training courses in painmanagement and developing pain assessment tools for assessing child's pain and evaluating the level of painmanagement procedures